Efficacy of a paper-based interleukin-6 test strip combined with a spectrum-based optical reader for sequential monitoring and early recognition of respiratory failure in elderly pneumonia—a pilot study - Chen, Cheng-Han; Fu, Yi-Chen; Lee, Yi-Tzu; Hsieh, Kai-Sheng; Shen, Ching-Fen; Cheng, Chao-Min (Frontiers in Pharmacology, 2023)
Community-acquired pneumonia (CAP) is lethal in elderly individuals who are more vulnerable to respiratory failure and require more emergency ventilation support than younger individuals. Interleukin-6 (IL-6) plays a crucial role and has predictive value in CAP; high serum IL-6 concentrations in adults are associated with high respiratory failure and mortality rates. Early detection of IL-6 levels can facilitate the timely stratification of patients at risk of acute respiratory failure. However, conventional enzyme-linked immunosorbent assay (ELISA) IL-6 measurement is laborious and time-consuming. The IL-6 rapid diagnostic system combined with a lateral flow immunoassay-based (LFA-based) IL-6 test strip and a spectrum-based optical reader is a novel tool developed for rapid and continuous bedside monitoring of serum IL-6 levels. Here, we evaluated the correlation between the IL-6 rapid diagnostic system and the ELISA and the efficacy of the system in stratifying high-risk elderly patients with CAP. Thirty-six elderly patients (median age: 86.5 years; range: 65–97 years) with CAP were enrolled. CAP diagnosis was established based on the Infectious Diseases Society of America (IDSA) criteria. The severity of pneumonia was assessed using the CURB-65 score and Pneumonia Severity Index (PSI). IL-6 concentration was measured twice within 24 h of admission. The primary endpoint variable was respiratory failure requiring invasive mechanical or non-invasive ventilation support after admission. IL-6 rapid diagnostic readouts correlated with ELISA results (P < 0.0001) for 30 samples. Patients were predominantly male and bedridden (69.4%). Ten patients (27.7%) experienced respiratory failure during admission, and five (13.9%) died of pneumonia. Respiratory failure was associated with a higher mortality rate (P = 0.015). Decreased serum IL-6 concentration within 24 h after admission indicated a lower risk of developing respiratory failure in later admission course (Receiver Operating Characteristic [ROC] curve = 0.696). Sequential IL-6 measurements with the IL-6 rapid diagnostic system might be useful in early clinical risk assessment and severity stratification of elderly patients with pneumonia. This system is a potential point-of-care diagnostic device for continuous serum IL-6 monitoring that can be applied in variable health care systems.